Efficient and Scalable Synthesis of 4-Carboxy-Pennsylvania Green Methyl Ester: A Hydrophobic Building Block for Fluorescent Molecular Probes - Woydziak, Zachary R.; Fu, Liqiang; Peterson, Blake R. (Synthesis, 2014)
Fluorinated fluorophores are valuable tools for studies of biological systems. However, amine-reactive single-isomer derivatives of these compounds are often very expensive. To provide an inexpensive alternative, we developed a practical synthesis of 4-carboxy-Pennsylvania Green methyl ester. Derivatives of this hydrophobic fluorinated fluorophore, a hybrid of the dyes Oregon Green and Tokyo Green, are often cell-permeable, enabling labeling of intracellular targets and components. Moreover, the low pKa of Pennsylvania Green (4.8) confers bright fluorescence in acidic cellular compartments, such as endosomes, enhancing its utility in chemical biology investigations. To improve access to the key intermediate 2,7-difluoro-3,6-dihydroxyxanthen-9-one, we subjected bis(2,4,5-trifluorophenyl)methanone to iterative nucleophilic aromatic substitution by hydroxide on scales in excess of 40 grams. The key intermediate was used to prepare over 15 grams of pure 4-carboxy-Pennsylvania green methyl ester in 28% overall yield without the use of chromatography. This compound can be converted into the amine-reactive N-hydroxysuccinimidyl ester in essentially quantitative yield for the synthesis of a wide variety of fluorescent molecular probes.
Keywords: fluorophore; bioorganic chemistry; chemical biology; molecular probes; fluorine; conjugation